PENGARUH KEPEMIMPINAN DAN PEMBERDAYAAN TERHADAP MOTIVASI DAN KINERJA PEGAWAI - Anuraga, I Putu Magna; Sintaasih, Desak Ketut; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.09.TAHUN 2017DO - 10.24843/EEB.2017.v06.i09.p05, 2017)
Performance is the result of work produced by employees in accordance with its role in the organization. Employee performance is one very important thing in a company to achieve the goal that every effort should be made to the company of increasing. This study aimed to analyze the influence of leadership and empowerment of employees on work motivation and performance of employees. This research was conducted at the Department of Education Youth and Sports Regency Tabanan using sample that 59 employees. Data were collected by conducting interviews and questionnaires. Subsequently collected data were analyzed using descriptive analysis and Partial Least Square. The results of this study concluded that the leadership is significant positive effect on work motivation. Empowerment is significant positive effect on employee performance and motivation. Work motivation is significant positive effect on employee performance. Furthermore, Leadership is not significant positive effect on employee performance.
Keywords: leadership, empowerment, motivation.performance